The Sweet Goodbye - Book 1 - Corbett, Ron, 1959- (Thorndike, Maine : Center Point Large Print, 2022)
"Something is not right in the North Maine Woods. A small family-run lumber company should not have more than two hundred million unaccountable dollars on their books. Money like that comes from moving something other than wood across the border. The first agent the FBI sent undercover was their best man--sure to get the answers that were needed. He was dead within a month. Now, Danny Barrett is taking his place. Before he was a cop, Danny grew up in the woods of Northern Michigan. He is the only chance the Feds have of getting answers, but how many more will have to die first?"--
Keywords: Barrett, Danny -- (Fictitious character) -- Fiction; Government investigators -- Fiction; Embezzlement -- Fiction; Conspiracies -- Fiction; Maine -- Fiction; Detective and mystery fiction; Fiction; Thrillers (Fiction); Thrillers (Fiction); Detective and mystery fiction